12 Theses for Understanding the Ethics of St. Clement of Ohrid (Annual of the Faculty of Philosophy in Skopje, 2018)
Culture and its range depend on the ethics of the people who create it. The conclusionis based on the experience in the creation of a culture in an area that gave the peoplein part of Europe literacy and new ways of understanding the world. Such was the ethicsof St. Clement of Ohrid...By giving us the letters, God commits us to doing good, and not evil. Realizing this,St. Clement did not find it difficult to move a step forward towards the bare acceptance ofthe ethical postulates by saying: It is not enough to simply run away from the evil, but oneshould also do good! This led to the creation of a code of conduct that is:- Ethics that offers knowledge;- Knowledge of God within oneself, for oneself;- Ethics of creating personal identity and recognizing and respecting the identitiesof others;The lack of such interdisciplinary thinking about this type of role of ethics in theseareas, as well as its consequences, represent open opportunities for a global clash of the cultures.
Keywords: ETHICS; EVIL; GOD; EDUCATION